Effect of pressure gradient and new phases for 1, 3, 5-trinitrohexahydro-s-triazine (RDX) under high pressures. Issue 21 (17th May 2018) - Gao, Chan; Zhang, Xueyong; Zhang, Chuanchao; Sui, Zhilei; Hou, Meng; Dai, Rucheng; Wang, Zhongping; Zheng, Xianxu; Zhang, Zengming
Abstract : Herein, pressure-induced phase transitions of RDX up to 50 GPa were systematically studied under different compression conditions. Abstract : Herein, pressure-induced phase transitions of RDX up to 50 GPa were systematically studied under different compression conditions. Precise phase transition points were obtained based on high-quality Raman spectra with small pressure intervals. This favors the correctness of the theoretical formula for detonation and the design of a precision weapon. The experimental results indicated that α-RDX immediately transformed to γ-RDX at 3.5 GPa due to hydrostatic conditions and possible interaction between the penetrating helium and RDX, with helium gas as the pressure-transmitting medium (PTM). Mapping of pressure distribution in samples demonstrates that the pressure gradient is generated in the chamber and independent of other PTMs. The gradient induced the first phase transition starts at 2.3 GPa and completed at 4.1 GPa. The larger pressure gradient promoted phase transition in advance under higher pressures. Experimental results supported that there existed two conformers of AAI and AAE for γ-RDX, as proposed by another group. δ-RDX was considered to only occur in a hydrostatic environment around 18 GPa using helium as the PTM. This study confirms that δ-RDX is independent of PTM and exists under non-hydrostatic conditions. Evidence for a new phase (ζ) was found at about 28 GPa. These 4 phases have also been verified via XRD under high pressures. In addition to this, another new phase (η) may exist above 38 GPa, and it needs to be further confirmed in the future. Moreover, all the phase transitions were reversible after the pressure was released, and original α-RDX was always obtained at ambient pressure.